2020
DOI: 10.1186/s13046-020-1534-z
|View full text |Cite
|
Sign up to set email alerts
|

Repurposing chlorpromazine in the treatment of glioblastoma multiforme: analysis of literature and forthcoming steps

Abstract: Background: Glioblastoma multiforme is a CNS cancer characterized by diffuse infiltrative growth, aggressive clinical behavior and very poor prognosis. The state-of-art clinical approach to this disease consists of surgical resection followed by radiotherapy plus concurrent and adjuvant chemotherapy with temozolomide. Tumor recurrence occurs in virtually all cases, therefore, despite any treatment, the median survival is very low (14.6 months), which makes the approach to these patients a challenging clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 10 publications
0
25
0
2
Order By: Relevance
“…Researchers in France reported that chlorpromazine, a derivative of methylene blue, inhibits SARS-CoV-2 in vitro and other studies have shown clinical benefit of chlorpromazine in the most invasive glial tumor, the grade IV astrocytoma, glioblastoma multiforme ( Amaral et al, 2004 ; Kamarudin and Parhar, 2019 ; Abbruzzese et al, 2020 ; Plaze et al, 2020 ). Methylene blue, the first synthetic compound in medicine has antimalarial properties, anti-SARS-Cov-2 properties, and a recent study reported the compound to be neuroprotective ( López-Muñoz et al, 2005 ; Poteet et al, 2012 ; Gendrot et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers in France reported that chlorpromazine, a derivative of methylene blue, inhibits SARS-CoV-2 in vitro and other studies have shown clinical benefit of chlorpromazine in the most invasive glial tumor, the grade IV astrocytoma, glioblastoma multiforme ( Amaral et al, 2004 ; Kamarudin and Parhar, 2019 ; Abbruzzese et al, 2020 ; Plaze et al, 2020 ). Methylene blue, the first synthetic compound in medicine has antimalarial properties, anti-SARS-Cov-2 properties, and a recent study reported the compound to be neuroprotective ( López-Muñoz et al, 2005 ; Poteet et al, 2012 ; Gendrot et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Repurposing CPZ exhibited much advantage in various cancers including glioblastoma, lung cancer, colon cancer and breast cancer (18)(19)(20). There were no relevant studies of CPZ in endometrial cancer at present.…”
Section: Discussionmentioning
confidence: 96%
“…CPZ was well-known as an antagonist of dopamine receptor D2(DRD2) (18). It was reported that dopamine acting through DRD2, down regulated insulin-like growth factor-1 (IGF-1) and AKT phosphorylation, thereby inhibited gastric cancer proliferation (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations